2012
DOI: 10.4103/1319-3767.103425
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of viral hepatitis in Saudi Arabia: Are we off the hook?

Abstract: Some 400 million people worldwide are currently infected with the hepatitis B virus (HBV), and the infection is common in the Middle East. Another 170 million people around the globe presently live with chronic hepatitis C virus (HCV) infection. Both HBV and HCV represent a worldwide epidemic. Despite significant decline in the prevalence of HBV and HCV infection in Saudi Arabia, these viral diseases cause significant morbidity and mortality, and impose a great burden on the country's healthcare system. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 50 publications
(70 reference statements)
10
123
7
Order By: Relevance
“…Furthermore, rates of hypertension, hypercholesterolemia, type 2 diabetes, arthritis problems, and cancer have all increased dramatically in recent years among Saudi citizens [11,12]. These unhealthy diets, smoking, lack of sufficient physical activity, chronic viral infections, and lack of knowledge about cancer and its prevention and screening methods have resulted in rising burden of cancer reported as one of the fastest growing health concerns in the KSA [12,13,14,15]. Based on this increasing cancer burden in the KSA, there is a need for cancer prevention based on healthy lifestyle programming and educational activities for the Saudi population.…”
Section: Saudi Arabian Healthcare Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, rates of hypertension, hypercholesterolemia, type 2 diabetes, arthritis problems, and cancer have all increased dramatically in recent years among Saudi citizens [11,12]. These unhealthy diets, smoking, lack of sufficient physical activity, chronic viral infections, and lack of knowledge about cancer and its prevention and screening methods have resulted in rising burden of cancer reported as one of the fastest growing health concerns in the KSA [12,13,14,15]. Based on this increasing cancer burden in the KSA, there is a need for cancer prevention based on healthy lifestyle programming and educational activities for the Saudi population.…”
Section: Saudi Arabian Healthcare Systemmentioning
confidence: 99%
“…In 2013, there were 495 cases of liver cancer accounting for 4.3% of all newly diagnosed cases [18]. This incidence of liver cancer in the KSA is not unexpected due to the high prevalence of chronic infections with hepatitis B and hepatitis C viruses among the Saudi population which is a precursor for liver cancer [13]. This cancer ranked fourth in males and eighth in females and affected 339 (68.5%) males and 159 (32.1%) females with a male to female ratio of 213:100 as of 2013.…”
Section: Cancer Epidemiology In the Kingdom Of Saudi Arabiamentioning
confidence: 99%
“…It has been reported that other regions such as Southeast Asia have a higher prev-alence of this type of infection and the rates vary across the ME (6,8). The prevalence of HCV infections in Iran and Israel is about 0.5% (9) and 1.96% (10), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The global rate of new HAV infections is approximately 1.4 million cases per year (6). However, despite its prevalence across the world, updated data about HAV infections in the ME, including their burdens and seroprevalence, are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation